(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Computerization of banking has received high importancein the recent years. Indian banking industry today is in the midst of an ITrevolution. A combination of regulatory and competitive forces has led toincreasing importance of total banking automation in the Indian bankingindustry. Hence there is a paradigm shift in banking in India as they startedto realize the need to be ‘Customer focused’ which is imperative for survivaland growth. Many aspects of information technology ATMs, tele- banking, mobilebanking, internet banking along with consumer durable loans, home loans,insurance, demat services etc have started taking place, especially after theentry of private and foreign banks which had advantage of the latesttechnology.